2017
DOI: 10.5114/fmpcr.2017.69291
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of insomnia and daytime somnolence among professional drivers

Abstract: Background. insomnia is described as an insufficient amount or quality of sleep that lasts for at least a month. sleeplessness in the group of professional drivers may lead to accidents and other road incidences. factors influencing the work of drivers include their work time -the amount of time they spend driving their vehicle. Objectives. the aim of the study was to estimate the frequency of the occurrence of insomnia among professional drivers, taking into consideration daytime sleepiness, socio-demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…This is an important finding, especially considering the job demands faced by POs, because insomnia is related to lower mental health and social functioning [102]. Insomnia symptoms in the Polish sample were almost four times higher than in a sample of Polish professional drivers and nurses, also measured with the AIS [103,104]. Although the mean results for the total sample in the current study were lower than those reported by oncological patients, the difference was 3% for the current Polish sample, with POs reporting higher insomnia scores [105].…”
Section: Discussionmentioning
confidence: 89%
“…This is an important finding, especially considering the job demands faced by POs, because insomnia is related to lower mental health and social functioning [102]. Insomnia symptoms in the Polish sample were almost four times higher than in a sample of Polish professional drivers and nurses, also measured with the AIS [103,104]. Although the mean results for the total sample in the current study were lower than those reported by oncological patients, the difference was 3% for the current Polish sample, with POs reporting higher insomnia scores [105].…”
Section: Discussionmentioning
confidence: 89%
“…zajmowała się problemem ryzyka zaśnięcia kierowcy podczas jazdy. W ich badaniu brało udział 94 kierowców zawodowych ocenianych za pomocą skali Epworth i autorskiego kwestionariusza, aż 34% ankietowanych przyznało, że stworzyli realne zagrożenie dla ruchu drogowego w trakcie pracy zawodowej, a 15,96% wykazywało łagodną nadmierną senność [17].…”
Section: Dyskusjaunclassified